Análise citogenética e investigação molecular do gene RASSF1A em indivíduos com síndrome mielodisplásica - Monteiro, Fernanda de Souza [UNESP] (2014)
The myelodysplastic syndromes (MDS) are characterized by cytopenias, dysplasia in one or more myeloid cell lines, ineffective hematopoiesis and an increased risk of acute myeloid leukemia (AML) transformation. The rate of patients who progress to AML varies by subtype of disease, according to the World Health Organization classification. The MDS are considered premalignant diseases and unlike of other hematological diseases, such as leukemia, are mostly associated with unbalanced chromosomal abnormalities, as deletions, translocations and numerical changes, beyond loss of genetic material with consequent tumor suppressor genes inactivation, which can control biological mechanisms such as DNA repair, growth and programmed cell death. An example is the tumor suppressor RASSF1A (Ras-association domain family 1, isoform A) mapped in 3p21.3. The high mutation rates and no expression of this gene, mainly exons 3, 4 and 5, have been described in several types of cancer but have never been investigated in MDS. Thereby chromosomal changes and mutations in exons 3, 4 and 5 from RASSF1A of the bone marrow cells from 50 cases the diagnosis of MDS were investigated. The assays were accomplished for 24 hours applying bone marrow cells without mitogenic stimulation and the exons were straight sequenced, where four samples (8%) had chromosomal abnormalities, characterized for hypodyploidy (two cases), monosomy 7 and complex karyotype involving chromosomes 3, 5 and 11. Molecular analysis revealed two (4%) other cases with Ala133Ser polymorphism (A133S) in exon 3. The cytogenetic changes observed are related to the MDS developed, while the polymorphism has been proposed to be involved in some types of cancers predisposition. The results can support other studies which are searching for genetic factors involved in the pathogenesis of MDS